Stumbling on Hybridity’s Playground: Exploring Design-Centric Thinking, Media Boundaries and Limitation in A Hybrid Text Space. - Goldberg, Peta Nicole (University of the Witwatersrand, Johannesburg, 2023)
This research posits an experimental thesis statement; “creative hybridity is a boundary-making event”. The dissertation takes place through an active narrative of experimentation playing with the ideas of how creativity engenders itself through hybridity and identity of medium. Using a design-centric outlook as well as a practice rooted, and at times spatio-visual thinking, the research posits that creative production (that is hybrid) bounds itself to patterns and structure to be recognized. The dissertation uses the case study ‘S.’ by J.J. Abrams and Doug Dorst (2013), a multimodal literature case study to explore hybridity, more specifically design production, through the lens of the thesis statement.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts (Digital Arts), to the Faculty of Humanities, Wits School of Arts, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Creative practice; Research design; Boundary; Limitation; Hybridity in research; S.; Hybrid Literature; UCTD; SDG-9: Industry, innovation and infrastructure